The Use of Storytelling in Virtual Reality for Studying Empathy: A Review - Christofi, Maria; Hadjipanayi, Christos; Michael-Grigoriou, Despina (My University, 2022)
This review focuses on the use of storytelling in immersive Virtual Reality (VR) for studying empathy and seeks to examine the areas in which storytelling has been integrated in the selected manuscripts and how effective these interventions were. Findings indicate the rise of research in this area in the last decade. The most dominant narrative themes for inducing empathy were found to be narratives regarding mental and physical abuse victims, minorities and immigrants and people with a health syndrome, disease or disorder. Regarding the effect on empathy in comparison studies with other narrative methods, the VR method did not show a significant advantage over the other narrative methods. In the studies where only a VR method was used, the results were shown to be more promising. Moreover, this review also highlights the use of embodiment and perspective-taking, and the ways interaction was integrated in the studies.